PEMBERDAYAAN PENGRAJIN BATIK KENDALUNTUK MENDUKUNG PARIWISATA - Syamwil, Rodia; Nurrohmah, Siti; Wahyuningsih, Urip (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2015)
Kendal regency government committed to develop tourism, through batik as one of their local potentials. Situation analysis in two micro-scale industry partners identify that both locate in tourism destination area, however their competitiveness to support tourisms need to be enhanced. Their motif collections with typical Kendal were limited, as well as product diversification,and environment support. One of the industry use natural dyes with high dependence to other province cultivation and high cost, while the other need applied technology of souvenir batik crafts,batik packaging, and patterned batik fashion. Solution offered was tourism awareness and environment collaboration agenda to strengthen industries through training, workshops, and technical assistance in: (1) development of typical regional motif; (2) producing souvenirs and packaging; (3) batik patterned dress; (4) batik with natural dyes based on research; (5) excellent service and simple communication in English. Product exhibition was conducted at the end of project. The results of the implementation of the activities showed an increase in knowledge, skills, and attitudes of the drilled material, creative product quality, while all participants affirmed their satisfaction.